2021
DOI: 10.21037/atm-20-7929
|View full text |Cite
|
Sign up to set email alerts
|

A narrative review of circular RNAs as potential biomarkers and therapeutic targets for cardiovascular diseases

Abstract: Circular RNAs (circRNAs), a novel class of non-coding RNA, are produced by back-splicing and were initially considered to be by-products of splicing. In recent years, computational technology and experimental evidence have revealed the tremendous amounts and potential physiological or pathological functions of this novel non-coding RNA species. At present, the roles of circRNAs in neurological diseases, immune diseases, and cancers have come to light. In addition, increasing studies have identified the express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 84 publications
0
8
0
Order By: Relevance
“…Considering the highly conserved and stable circRNAs, it has become a target for the diagnosis and treatment of many diseases ( 19 21 ). A previous study identified that several dysregulated circRNAs were in the murine liver at the early stage of E. multilocularis infection, which indicated important roles that DE-circRNAs have played ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the highly conserved and stable circRNAs, it has become a target for the diagnosis and treatment of many diseases ( 19 21 ). A previous study identified that several dysregulated circRNAs were in the murine liver at the early stage of E. multilocularis infection, which indicated important roles that DE-circRNAs have played ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…confirmed that the great majority of circRNAs were long-lived compared with linear mRNAs ( 34 ), as the half-life of circRNAs exceed 48 h while that of linear is less than 20 h ( 26 ); (2) abundance: Next-generation RNA sequencing corrected the early false assumption that circRNAs were errors with non-function and low expression during transcription. Numerous studies have been devoted to considering the expression and function of circRNAs ( 26 , 30 , 35 , 36 ). Generally, the expression level of most circRNAs is only 5-10% of its linear transcript ( 37 ).…”
Section: Backgrounds Of Circrnas: Classification Biogenesis and Featuresmentioning
confidence: 99%
“…In addition to adult tissues, circular RNA has been discovered in developing tissues [ 11 , 12 , 13 ]. In recent years, circRNAs have emerged as important regulatory molecules for cardiovascular and pulmonary development, as well as diseases of aberrant development [ 11 , 12 , 14 , 15 , 16 , 17 , 18 , 19 ]. Recent research has proven that genetic factors play an integral role in the progression of developmental lung diseases such as bronchopulmonary dysplasia (BPD) [ 7 , 20 ] and neonatal acute respiratory distress syndrome (ARDS).…”
Section: Introductionmentioning
confidence: 99%